Seven-day ischaemic preconditioning improves muscle efficiency during cycling - Mark Waldron (Journal of Sports Sciences, 2019)
Ischaemic preconditioning (IPC) has emerged as a potential non-invasive ergogenic aid to enhance exercise performance. Repeated application of IPC has demonstrated clinical efficacy, therefore our aims were to investigate its effect on endurance cycling performance and muscle efficiency. Twenty participants undertook 7-d repeated bilateral lower limb occlusion (4 x 5-min) of IPC (220 mmHg) or sham (20 mmHg). Prior to and 72-h following the intervention, participants performed submaximal cycling at 70, 80 and 90% of ventilatory threshold (VT) followed by an incremental exercise test. IPC had no effect on VO2max (P = 0.110); however, time to exhaustion increased by ~ 9% and Wmax by ~ 5 % (IPC pre 307 ± 45 to post 323 ± 51 W) relative to sham (P = 0.002). There were no changes in gross efficiency (GE) (P > 0.05); however, delta efficiency (DE) increased by 3.1% following IPC (P = 0.011). Deoxyhaemoglobin (HHb) was reduced following IPC ~ 30% (P = 0.017) with no change in total haemoglobin (tHb). Repeated IPC over 7-d enhanced muscle efficiency and extended cycling performance. The physiological effects of repeated IPC on skeletal muscle efficiency explains the notable improvements in endurance performance.